Classify, Measure, Tabulate: Exploring Teacher Strategies in Shaping Scientific Process Skills in Phase Change Physics - Farni, Evi Ramna; Pramitha, Sarah (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to explore and describe the strategies used by physics teachers to enhance students’ scientific process skills specifically in classifying, measuring, and tabulating data during the learning of phase changes of matter in senior high school. Methodology: This study employed a qualitative naturalistic approach. Data were collected using in-depth interviews and photographic documentation. The participants included one physics teacher and 36 students of class XI F7 Senior High School 10 Jambi City. Istruments used were interview guidelines and documentation sheets. Data analysis followed the stages of data reduction, data display, and conclusion drawing. Main Findings: The study found that teachers implemented various strategies to improve students’ scientific process skills, particularly in classifying, measuring, and constructing data tables during the learning of phase changes of matter. Through structured guidance, contextual examples, and supportive assessments, students showed improved accuracy and independence in scientific data handling. Both teacher and student responses indicated that strategy-based teaching effectively enhanced students’ analytical and practical competencies in physics learning. Novelty/Originality of this study: This study offers a fresh perspective by exploring teacher strategies specifically designed to enhance students’ abilities in classifying, measuring, and tabulating data within the topic of phase changes in physics. Unlike previous research, it integrates pedagogical, methodological, and model-based approaches, contributing new insights into the development of scientific process skills in secondary education settings.